PAKISTAN'S DUAL ROLE IN THE GLOBAL WAR ON TERRORISM: CONTRIBUTIONS AND IMPACTS - Zulfiqar Khan; Shahla Ayub (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistan's complex involvement in the Global War on Terror, examining its role as both a frontline ally in combating terrorism and a breeding ground for extremist elements. It analyzes the impacts of Pakistan's strategic decisions on its internal security dynamics, regional stability, and contributions to the global fight against terrorism. This study investigates Pakistan's complex engagement in the Global War on Terror, exploring its role as both a vital ally in counterterrorism efforts and a nation contending with internal security issues exacerbated by extremist factions. This qualitative research explores Pakistan's complex role in the Global War on Terror, analyzing its impacts and contributions through extensive data collection and analysis. Pakistan's role in the Global War on Terror underscores the complex interplay of geopolitical interests, national security concerns, and international diplomacy, with profound impacts on its security landscape. Pakistan should prioritize strengthening diplomatic ties, continuing counterterrorism efforts, and fostering socio-economic development to address extremism and terrorism effectively.